BEBERAPA FAKTOR YANG BERHUBUNGAN DENGAN KETEPATAN PASIEN DI RUANG IGD - Efendi, Suradi; Sarimin, Dorce Sisfiani; Purnomo, Heru; Mu'awanah, Mu'awanah (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: The Emergency Department (ED) is one of the important components in the health care system in hospitals, which has a central role in providing initial treatment to patients who are in critical condition or require immediate medical action. The purpose of the study was to determine several factors associated with the accuracy of patients in the emergency room. The research design used in this study was cross sectional. The research was conducted at Premier Surabaya Hospital. The research was conducted in June 2024. The population in this study were all nurses who served in the Emergency Room of Premier Hospital totaling 20 people. The sample amounted to 19 people. The sampling technique used Simple Random Sampling technique. Data analysis was carried out univariate and bivariate. The results showed a relationship between length of work (p value: 0.02) and there was no relationship between education (p value: 0.716) on the accuracy of patient handling. It is recommended that the hospital can provide special training for emergency room nurses, in order to hone the ability of emergency room nurses to be able to handle appropriately, quickly and measurably.Keywords: Emergency Department, Length Of Service, Education.